A case of Toxic Methaemoglobinemia by Dapsone Poisoning - Sen, Sendip; Chatterjee, A; Gyan, G (Journal of College of Medical Sciences-Nepal, 2014)
Dapsone (4,4-diaminodiphenylsulfone) is a commonly used drug for leprosy, dermatitis herpetiformis, lichen planus, other skin diseases and pneumocystis jiroveci infection in HIV patient. Dapsone poisoining is accidental in children. We report such a case who presented with severe cyanosis and respiratory distress and was treated successfully with intravenous methylene blue. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 54-56 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9688